Changing prevalence of severe congenital heart disease: Results from the National Register for Congenital Heart Defects in Germany. (18th July 2017) - Pfitzer, Constanze; Helm, Paul C.; Ferentzi, Hannah; Rosenthal, Lisa‐Maria; Bauer, Ulrike M. M.; Berger, Felix; Schmitt, Katharina R. L.
Abstract: Objective: To assess the prevalence of congenital heart disease (CHD) in Germany in relation to phenotypes, severity and gender. Design: Cross‐sectional registry study. Setting: We analyzed data from patients with CHD born between 1996 and 2015. Patients: A total of 26 630 patients, registered with the NRCHD, were born between 1996 and 2015. 10 927 patients were excluded from the current analysis due to prior registration with the NRCHD under the German PAN Prevalence Study, which showed a potential bias in the inclusion of this patient population (proportion of mild cardiac lesions was comparatively high due to improved diagnostic capability for earlier identifying minor lesions). At least 15 703 patients with demographic data and detailed medical information were included in the current study. Interventions: None. Outcome Measures: Prevalence of CHD in Germany differentiated into gender, severity, and phenotype. Results: In total, 15 703 patients with CHD (47.1% female) were included in this study. The five most common phenotypes were found to be ventricular septal defect (19.2%), atrial septal defect (13.0%), Tetralogy of Fallot (9.3%), univentricular heart (9.4%), and coractation of the aortae (7.0%). The prevalence of CHD in regard to severity changed over the duration of the observation period. From 1996 to 2007, the number of simple CHD rose steadily ( P  < .001), whereas the number of severe CHD has grown significantly since 2008/2009 ( P  < .001). In regard to gender, the prevalence of simple CHD was higher in females, whereas complex lesions were more common in males ( P  < .001). Conclusions: Our study shows a growing number of registered severe CHD in the recent decade in Germany. This development is noteworthy as it implicates a growing demand for first intensive hospital care, expert pediatric cardiologic aftercare, and consequently higher economic impact for this patient population.